International youth mental health case study of peer researchers’ experiences - Inga Spuerck; Milos Stankovic; Syeda Zeenat Fatima; Elmas Yilmas; Nicholas Morgan; Jenna Jacob; Julian Edbrooke-Childs; Panos Vostanis (Research Involvement and Engagement, 2023)
Abstract Background The involvement of young people as peer researchers, especially with lived experience, is increasingly considered important in youth mental health research. Yet, there is variation in the understanding of the role, and limited evidence on its implementation across different research systems. This case study focusses on the barriers and enablers of implementing peer researcher roles within and across majority world countries contexts. Methods Based on an international youth mental health project involving different levels of peer researchers and participants from eight countries, peer researchers and a co-ordinating career researcher reflect on lessons regarding enabling and challenging factors. These reflections are captured and integrated by a systematic insight analysis process. Results Building on existing international networks, it was feasible to actively involve peer researchers with lived experience in a multi-country mental health study, who in turn recruited and engaged young participants. Identified challenges include the terminology and definition of the role, cultural differences in mental health concepts, and consistency across countries and sites. Discussion Peer researchers’ role could be strengthened and mainstreamed in the future through ongoing international networks, training, sufficient planning, and active influence throughout the research process. Trial registration: Not applicable.